MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI KPK DAN FPB DENGAN MEDIA BAMBU TONGCIN PADA SISWA KELAS IV SDN 3 TANJUNG - Hernayati, Rini (Vidya Karya Jurnal Kependidikan, 2014)
This research aimed to find out about âBambu Tonggak Bercincinâ media and its implementation in orderÂ to improve learning outcomes of mathematics learning materials about KPK Â and FPB in fourth grade. This classroom action research was conducted at SDN 3 Tanjung Kecamatan Tanjung for fourth grade students with 2 cycles. The subjects were 29 fourth grade students, consisting of 14 boy students and 15 girl students. The results showed that (1) there was an increase in mathematics achievement about FPB and KPK material on students after using âBambu Tonggak Bercincinâ media in learning. The average of student activity increased from 65.92 in the first cycle to 93.75 in second cycle, (2) the average of teacher activity Â increased from 83.34 in the first cycle to 97.88 in second cycle. (3) The average of Â student learning outcomes increased from 75.86 in the first cycle to 93.10 in second cycle. By using âBambu Tonggak Bercincinâ media in learning of KPK and FPB predefined indicators of success were reached when the average student activity was 79.83% with good category, the implementation of lesson plan/ the average of teacher activity was 90.61% with very good category, only two students who did not complete (6.90%), but the classical mastery reached 93.10%.